Seguimiento de la salinidad en suelos regados por pivotes centrales en 25 de mayo, La Pampa - Sartor, Paolo Daniel; Masseroni, Maria Lujan; Aumassanne, Carolina Manuela; Fontanella, Dardo Roy; Zamora, Carlos Damian; Alvarez, Cristian (Red Argentina de Salinidad, 2023)
Poster y resumen